Evaluating the Role of Wnt Signal Transduction in Promoting the Development of the Heart - Leonard M. Eisenberg; Carol A. Eisenberg (The Scientific World Journal)
Wnts are a family of secreted signaling proteins that are encoded by 19 distinct genes in the vertebrate genome. These molecules initiate several signal transduction pathways: the canonical Wnt, Wnt/Ca2+, and Wnt/planar cell polarity pathways. Wnt proteins have major impact on embryonic development, tumor progression, and stem cell differentiation. Wnt signal transduction also influences the formation of the heart, yet many issues concerning the involvement of Wnt regulation in initiating cardiac development remain unresolved. In this review, we will examine the published record to discern (a) what has been shown by experimental studies on the participation of Wnt signaling in cardiogenesis, and (b) what are the important questions that need to be addressed to understand the importance and function of Wnt signal transduction in facilitating the development of the heart.